Ex-husbands [videorecording (DVD)] - Dunne, Griffin; Arquette, Rosanna, 1959-; Benjamin, Richard, 1938- (Greenwich Entertainment, 2025)
Manhattan dentist Peter Pearce is facing a midlife crisis after his wife of 35 years leaves him. On the spur of the moment, he books a trip to Tulum, Mexico, only to crash his son's bachelor party.